EVALUASI DAMPAK PERDA KOTA SEMARANG NOMOR 7 TAHUN 2010 TENTANG PENATAAN RUANG TERBUKA HIJAU (RTH) DI KOTA SEMARANG (STUDI DI KECAMATAN MIJEN KOTA SEMARANG) - Eka Rofiyanti; Sri Suwitri; Ida Hayu D (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
RTH has provide benefits on the quality of an urban environment so as to need an attempt to maintain and improve the quality of the environment through the provision of green open space (RTH) adequate. To support the arrangement of green space (RTH) in Kota Semarang then formed perda kota semarang No. 7 tahun 2010 tentang penataan RTH. Although the implementation of this regulation has created a new green space area and there have been a reduction in activity development as the impact of the output of perda Kota Semarang No. 7 tahun 2010 tentang penataan RTH, but not equal in every region in the Kota Semarang. So the purpose the arrangement related to the fulfillment of green space area achievement of green open space by up to 30 % yet could be met. The study is done in kecamatan Mijen as one of the areas with the highest green space area in kota Semarang whose aim is to give clear evidence about the impact of Perda Kota Semarang No. 7 tahun 2010 tentang penataan RTH in Kota Semarang on the community in Kecamatan Mijen. Research shows that the implementation of Perda Kota Semarang No. 7 tahun 2010 tentang penataan RTH in kota Semarang no major impact on the social life of the community in Kecamatan Mijen .